Clinicopathological Characteristics and Prognosis of Signet Ring Gastric Cancer: A Population-Based Study - Wei, Qing; Gao, Yiding; Qi, Changsong; Yuan, Xing; Li, Jingjing; Xu, Qi; Luo, Cong; Chen, Lei; Zhuo, Wei; Xu, Zhiyuan; Ying, Jieer (Frontiers in Oncology, 2021)
Background: To better define the clinicopathologic characteristics of signet ring cell (SRC) gastric cancer and build a prognostic model for it. Methods: SRC patient information from 2010 to 2015 were identified using Surveillance, Epidemiology, and End Results (SEER) database. Kaplan-Meier method and log-rank test were used to estimate Overall survival (OS) and to determine associations with histologic subtypes. In COX proportional hazards regression model-based univariate and multivariate analyses, significant variables for construction of a nomogram were screened out. The nomogram was validated by means of the concordance index (CI), calibration plots, as well as receiver operating characteristics (ROCs) curves. Results: A total of 11,363 gastric cancer patients were enrolled. On dividing the patients into SRC, well-to-moderately differentiated (WMD) adenocarcinoma, and poorly differentiated (PD) adenocarcinoma, differences among these subgroups emerged. SRC patients were more likely to occur in female and young patients than other histologic subtypes. Larger tumors, stage T4, and node stage N3 were more likely to be found in the SRC group. The survival for SRC patients was better than non-SRC patients in stage I. Univariate and multivariate analyses identified age, tumor site, larger tumor size, advanced T classification, advanced N classification, advanced TNM stage, and surgery of primary site as independent prognostic indicators. Then an OS nomogram was formulated. Conclusions: SRC had distinct clinicopathological characteristics. The nomogram provided an accurate tool to evaluate the prognosis of SRC.